Comparison of mean temperature taken between commercial and prototype thermal sensor in estimating mean temperature of oil palm fresh fruit bunches - Zolfagharnassab, Shahrzad; Vong, C. N.; Mohamed Shariff, Abdul Rashid; Ehsani, Reza; Jaafar, Hawa Z. E.; Aris, Ishak (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Thermal imaging is widely utilized in agricultural applications such as examining plant physiology, yield prediction, irrigation scheduling, bruises and pathogen determination in fruits and vegetables. There is a need for a cost effective thermal device for this wide range of applications. In this study, a low-cost prototype thermal device was used to measure the temperature of FFBs at three maturity levels, that are under-ripe, ripe and over-ripe. The experiment was repeated using a commercial thermal camera. Then, the mean temperature obtained from both the prototype and commercial thermal sensors was compared. Our results showed the prototype thermal device is capable of estimating the mean temperature of oil palm FFBs with the values analogous to the mean temperature from commercial thermal camera with R2 = 0.71.